2017
DOI: 10.21511/ppm.15(2-2).2017.08
|View full text |Cite
|
Sign up to set email alerts
|

The risk management practices in the manufacturing SMEs in Cape Town

Abstract: Risk management is one of the prominent issues which are pivotal to the success of a business and may adversely affect profitability if not properly practised. Therefore, the main objective of this paper was to determine risk management practices in manufacturing SMEs in Cape Town. The research conducted was quantitative in nature and constituted the collection of data from 74 SME leaders, all of whom had to adhere to a list of strict delineation criteria. All data collected were thoroughly analyzed through me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…His research confirms that effective risk management is essential for capital management. Be that as it may, Sifumba et al (2017) have found that the managers of SMEs are generally unaware of what makes risk management effective and that this hinders the development of SMEs, perpetuating the problems they face. Notwithstanding reports of lack of management or limited expertise and CG practice at SMEs, Arslan & Alqatan (2020), Hooghiemstra (2012), Hove-Sibanda et al (2017, Ledwaba (2017), Phiri (2011, p. 25) and Sarah (2017) have found that a solution is possible in the application of CG practice at the SMEs to enhance managerial competence.…”
Section: Lack Of Expertise In Cg Risk Management and Management Of Au...mentioning
confidence: 99%
“…His research confirms that effective risk management is essential for capital management. Be that as it may, Sifumba et al (2017) have found that the managers of SMEs are generally unaware of what makes risk management effective and that this hinders the development of SMEs, perpetuating the problems they face. Notwithstanding reports of lack of management or limited expertise and CG practice at SMEs, Arslan & Alqatan (2020), Hooghiemstra (2012), Hove-Sibanda et al (2017, Ledwaba (2017), Phiri (2011, p. 25) and Sarah (2017) have found that a solution is possible in the application of CG practice at the SMEs to enhance managerial competence.…”
Section: Lack Of Expertise In Cg Risk Management and Management Of Au...mentioning
confidence: 99%
“…In turn, (Sifumba et al, 2017) states that risk management is one of the most important issues being the key for business success, but can negatively affect the profitability if not realized properly. (Klimenko, 2013) believes that industrial enterprise risk management should be implemented by using a cumulative approach based on the bifurcation nature of industrial development.…”
Section: Literature Reviewmentioning
confidence: 99%